Influence of Ion Viscosity on the Distributions of Plasma Parameters in Stationary Gas Discharge - Leleko, Ya.F.; Grekov, D.L. (Ukrainian Journal of Physics, 2021)
On the basis of hydrodynamic equations, the distributions of such plasma parameters as the electric potential, the ion and electron densities, and the ion fl ow velocity toward the wall in a plane layer of the stationary weakly ionized non-isothermal plasma confi ned between the dielectric walls have been obtained. The temperatures of ions and electrons, as well as the density of neutrals, are assumed to be constant. Instead of fi nding the eigenfunctions and eigenvalues of the described problem, the Cauchy problem is solved with the initial values corresponding to those that are in the plasma bulk. The wall position is determined from the balance condition for the ion and electron fl uxes. A method to avoid the singularity in the system of hydrodynamic equations has been proposed. The infl uence of the ion viscosity in the equation of ion motion was estimated. The distributions of plasma parameters are obtained considering the ion viscosity in a quasineutral region.